2016
DOI: 10.1007/s10897-016-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Amyotrophic Lateral Sclerosis Have High Interest in and Limited Access to Genetic Testing

Abstract: Although genetic testing for amyotrophic lateral sclerosis (ALS) is widely available, it is unknown what proportion of patients with ALS have access to genetic counseling and testing, and patient attitudes towards ALS genetic testing have not been studied. We conducted a national survey of ALS patients enrolled in the Agency for Toxic Substances and Disease Registry, which consisted of multiple choice questions and two 12 item Likert scale series assessing respondents' experience with and attitude toward genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 18 publications
(19 reference statements)
1
39
0
1
Order By: Relevance
“…. However, ALS patients have reported difficulty accessing genetic testing 92. Indeed, studies have yet to estimate the proportion of the ALS population that engage with genetic testing and genetic counseling.…”
Section: Introductionmentioning
confidence: 99%
“…. However, ALS patients have reported difficulty accessing genetic testing 92. Indeed, studies have yet to estimate the proportion of the ALS population that engage with genetic testing and genetic counseling.…”
Section: Introductionmentioning
confidence: 99%
“…We also examined whether seeing a genetic counselor was associated with a more positive test experience. Survey data collected on ALS patient attitudes indicated that patients who reported contact with a genetic counselor had more positive attitudes regarding the potential benefits of genetic testing for patients, the medical community, and society (Wagner et al., ). However, we found that seeing a genetic counselor was not associated with more positive test experience scores in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…All results were tabulated and exported in .xls and/or .csv format for analysis. The survey instrument was described in detail previously (Wagner et al, 2016), and is available in Supporting Information. Those respondents who were offered and had genetic testing were given additional questions addressing outcome of their genetic testing and disclosure of results.…”
Section: Ethical Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic counseling should be offered routinely to all ALS patients [78], ideally through accessing ALS MDCs. The addition of genetic counselors to the clinical team enables patients to receive specialized advice in a supportive environment dedicated to ALS care.…”
Section: Future Perspectivementioning
confidence: 99%